1994
DOI: 10.1175/1520-0477(1994)075<0811:caotum>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Climatic Aspects of the 1993 Upper Mississippi River Basin Flood

Abstract: The 1993 record-breaking summerflood in the Upper Mississippi River Basin resulted from an unprecedentedly persistent heavy rain pattern. Rainfall totals for the Upper Mississippi River Basin were, by a large margin, the largest of this century for the 2-, 3-, 4-, and 12month periods encompassing the 1993 summer. The totals for these periods are estimated to have a probability of occurrence of less than 0.005 yr\ In addition, the number of reporting stations receiving weekly totals in excess of 100 mm (events … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
97
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(99 citation statements)
references
References 8 publications
2
97
0
Order By: Relevance
“…The 2008 (Kunkel et al, 1994); in 2008 the area extended eastwards into Indiana with flooding reported along the Wabash River. This paper demonstrates that these differences in the timing and duration of flood occurrence in both years, as well as the geographic area impacted by the floods, can be accounted for by the antecedent surface and atmospheric conditions, and the evolution of the state the subsequent large-scale circulation patterns associated with the flooding.…”
Section: Discussionmentioning
confidence: 99%
“…The 2008 (Kunkel et al, 1994); in 2008 the area extended eastwards into Indiana with flooding reported along the Wabash River. This paper demonstrates that these differences in the timing and duration of flood occurrence in both years, as well as the geographic area impacted by the floods, can be accounted for by the antecedent surface and atmospheric conditions, and the evolution of the state the subsequent large-scale circulation patterns associated with the flooding.…”
Section: Discussionmentioning
confidence: 99%
“…Although details of these events may vary, such as the Midwest floods of 1993 (e.g., Kunkel et al 1994) and 2008(e.g., Coleman and Budikova 2010, there is no question that these events cause immense social and economic stress to those that are affected. Furthermore, very heavy precipitation events are often highly localized in time and space and can occur independently from changes in the seasonal mean, making these events difficult to predict (Gershunov 1998;Kunkel et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Extended periods of substantial precipitation represented by monthly extremes can produce widespread episodes of flooding (e.g., Kunkel et al 1994). We focus on simulations of contemporary climate produced by a set of regional climate models (RCMs) that simulated a common period and domain for the North American Regional Climate Change Assessment Program (NARCCAP) (Mearns et al @@ Deceased. 2009).…”
Section: Introductionmentioning
confidence: 99%